Long Non-Coding RNA-TMPO-AS1 as ceRNA Binding to let-7c-5p Upregulates STRIP2 Expression and Predicts Poor Prognosis in Lung Adenocarcinoma - Wang, Juan; Yuan, Yixiao; Tang, Lin; Zhai, Haoqing; Zhang, Dahang; Duan, Lincan; Jiang, Xiulin; Li, Chen (Frontiers in Oncology, 2022)
Background Striatin-interacting protein 2 (STRIP2), also called Fam40b, has been reported to regulate tumor cell growth. But the role of STRIP2 in lung adenocarcinoma (LUAD) has not been discovered clearly. Thus, the aim of our study is to explore the function and underlying mechanism of STRIP2 in LUAD. Methods Expression of STRIP2 was determined using the Cancer Genome Atlas (TCGA), GTEx, Ualcan, and the Human Protein Altas databases. The Correlation of STRIP2 and survival was detected by PrognoScan and Kaplan–Meier plotter databases. Besides, the correlation between STRIP2 expression and tumor immune infiltration as well as immune checkpoints were analyzed by the ssGSEA method. The biological function of STRIP2 and its co-expression genes was determined by gene ontology (GO) and Genes and Genomes (KEGG), respectively. Finally, the expression level and biological function of STRIP2 in LUAD were determined by qPCR, CCK8, transwell, and wound healing assays. Results This manuscript revealed a significantly increased expression of mRNA and protein of STRIP2 in lung adenocarcinoma compared with the adjacent normal tissues. GEO and Kaplan–Meier plotter databases showed higher STRIP2 expression levels were correlated with poor prognosis survival of LUAD. Moreover, Cox regression analysis suggested that a higher STRIP2 level served as an independent risk factor in predicting deteriorative overall survival (OS) for LUAD patients. SsGSEA results showed STRIP2 expression level was positively correlated with infiltrating levels of Th2 cells in LUAD. Lastly, GO analysis indicated the biological processes were enriched in nuclear division and positive regulation of the cell cycle. KEGG signaling pathway analysis showed STRIP2 was correlated with the MAPK signaling pathway and the TNF signaling pathway. The GSEA database showed that STRIP2 was positively associated with the epithelial–mesenchymal transition, cell cycle, and TNF signaling pathway. The QRT-PCR assay showed that STRIP2 was upregulated in LUAD cell lines. Cell proliferation and migration were inhibited in LUAD by knockdown of STRIP2. Moreover, we confirmed that the TMPO-AS1/let-7c-5p/STRIP2 network regulates STRIP2 overexpression in LUAD and is associated with poor prognosis. Conclusion Our findings indicated that STRIP2 acted as a crucial oncogene in LUAD and was correlated with unfavorable survival and tumor infiltration inflation.